DESAIN KOLABORASI PENYEDIAAN LAYANAN PEMERINTAHAN BERBASIS OPEN GOVERNMENT - Maulana, Rio Yusri (Jurusan Ilmu Sosial dan Ilmu Politik Fakultas Hukum Universitas Jambi, 2018)
This study looks at the extent to which government collaboration and public involvement in service delivery by the Jambi Provincial Government, in its course of governance continues to move in the service sector which can be directly accessed by the public, not only as recipients, but also as a source of services. To accelerate this process, the government is transformed into instant and practical with the concept of e-government, implementing governance with the principle of collaboration, utilizing technology, and information services produced can be accessed by anyone in an open / Open Government manner. However, this understanding of government has not been fully responded to in response both in the community and the government itself. By using a qualitative approach and descriptive method, the authors hope to obtain the empirical relationship behind the phenomenon by obtaining a profound, thorough, detailed and complete meaning. Therefore the use of a qualitative approach in this study is to match, compare, and look for the red thread between empirical reality and the prevailing theory. The findings in this study are the absence of a clear collaboration design and the low level of understanding among service providers in government regarding mechanisms, methods, and innovation processes that aim to be able to involve the public effectively, either as recipients or sources of services. This is due to the lack of commitment from leaders at the elite level, and organizational culture that is still static, not dynamic. And the availability of budget and supporting infrastructure that is still minimal. Then more effective collaboration is needed by being encouraged by improving regulations, structuring and improving the quality of human resources, and commitment to the provision of budgets and supporting infrastructure for electronic-based services. So if all these elements can be fulfilled, the implementation of a government based on open public engagement with open government design can be realized in Jambi Province.